From AVATAR Mice to Patients: RC48-ADC Exerted Promising Efficacy in Advanced Gastric Cancer With HER2 Expression - Chen, Zuhua; Yuan, Jiajia; Xu, Yingying; Zhang, Cheng; Li, Zhongwu; Gong, Jifang; Li, Yanyan; Shen, Lin; Gao, Jing (Frontiers in Pharmacology, 2022)
RC48-ADC is a novel humanized antibody specific for HER2 in conjugation with a microtubule inhibitor via a cleavable linker. This study was to evaluate the antitumor activity and mechanism of RC48-ADC in gastric cancer (GC), as well as explore the population who may benefit from RC48-ADC treatment. Four human GC cell lines and nine patient-derived xenograft (PDX) models were exploited to evaluate antitumor effect of RC48-ADC or trastuzumab treatment in vitro and in vivo. The expression and phosphorylation of HER2 were assessed by immunohistochemistry (IHC) staining. Critical molecules of downstream PI3K/AKT, cell cycle and apoptosis signaling pathways were detected and quantified by immunoblotting. Combined with preliminary results of preclinical research, three patients with IHC3+, IHC2+/FISH+, and IHC2+/FISH- of HER2 were enrolled to verify the efficacy of RC48-ADC treatment in advanced GC. In vitro, RC48-ADC had superior antiproliferative effects in a dose-dependent manner on GC cells, especially on HER2-positive cells. In vivo, RC48-ADC exceeded trastuzumab in GC PDX models with HER2 expression, even in models with moderate to low expression of HER2. Further exploration of mechanism showed that RC48-ADC exerted the antitumor effect by inhibiting phosphorylation of HER2, inducing G2/M phase arrest and cell apoptosis in HER2-expressed PDX models. In clinical practice, RC48-ADC had satisfactory efficacy in HER2-positive and HER2 moderately expressed GC patients, and demonstrated promising efficacy in HER2-positive patients who have progressed after anti-HER2 therapy. In conclusion, RC48-ADC exerted promising antitumor activity in HER2-positive, as well as score of 2+ in IHC and ISH-negative AGC patients after progression of systematic treatment.